Smart Adaptive Traffic Light Prototype Using Ultrasonic Sensors and Arduino - Hamdi, Firman; Adeswastoto, Hanantatur; Joko Musridho, Raja (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Traffic congestion at intersections is often caused by traffic light systems that still rely on fixed timing without taking into account the number of vehicles. The purpose of this study is to create a prototype of a smart traffic light that can adapt automatically using ultrasonic sensors and Arduino. The method applied is Research and Development (RnD) with a prototype approach through the stages of design, assembly, and using a scaled prototype simulation. The results of the testing show that this system is capable of regulating the duration of the green light based on vehicle density, thereby improving the smooth flow of traffic at intersections.